Efeito da atorvastatina sobre as alterações comportamentais, histológicas e bioquímicas em camundongos C57BL/6 com status epilepticus induzido por pilocarpina - Oliveira, Clarissa Vasconcelos de (2017)
Epilepsy is a chronic neurological disease that affects 65 million people worldwide. Temporal lobe epilepsy (TLE) is the most common type of focal epilepsy in adults, and also the one with the highest refractoriness index to pharmacological treatment. In addition to epileptic seizures, patients with TLE suffer from medical comorbidities such as depression, anxiety, and cognitive impairment. Experimental models of epileptogenesis, such as model of TLE post-SE pilocarpine-induced, have greatly increased the understanding of the processes leading to epilepsy and, thus, potential targets for antiepileptogenic therapy. Considering the crucial role of inflammation in the development of epileptogenesis, it is believed that drugs that have anti-inflammatory effects would be an interesting strategy to prevent or reduce the consequences of epileptogenic brain insult. In this sense, statins, which are drugs used to treat dyslipidemias, present pleiotropic effects, including anti-inflammatory effect, which seems to be effective in preventing neuroinflammation and neuronal death in a variety of neurological diseases, including epilepsy. However, there are few studies on the effect of treatment with statins during the epileptogenic period. Thus, considering the potential neuroprotective effect of statins in different diseases of the central nervous system, the present study aims to evaluate the effect of treatment with atorvastatin at doses of 10 and 100 mg/kg on cognitive and behavioral changes, as well as on the susceptibility to seizures induced by PTZ during the epileptogenic process in mice submitted to the SE pilocarpine-induced. Considering the importance of the preclinical studies being developed in animals of both genders, male and female mice were used. The results show that the treatment with atorvastatin exerts a subtle disease-modifying effect, raising the convulsive threshold of the animals and improving in part the cognitive deficits, which seem to be related to its anti-inflammatory effect. In addition, the protective effects were similar in both female and male mice, except for the fact that a high dose of atorvastatin was required for females. These data reinforce the importance of developing preclinical studies in animals of both sexes. However more studies are needed to evaluate the potential effect of this statin in the treatment of epilepsy.